An Analysis of Factors Influencing Decisions of Passengers on Citilink Indonesia Flight Routes Semarang - Jakarta (Studies at General Ahmad Yani International Airport, Semarang) - Adenanthera Lesmana Dewa; Niken Adriana R. Ully; Andar Sri Sumantri (Universitas Veteran Bangun Nusantara, 2023)
Passenger Decision is a process that involves identifying needs, seeking information, evaluating alternatives, making a decision, and evaluating behavior after using a service. The General Ahmad Yani International Airport in Semarang is one of the international airports in Central Java Province. This study aims to determine the effect of Brand Image, Timeliness, Service Quality, and Perceived Price variables on Citilink Passenger Decisions at General Ahmad Yani International Airport. The study used 100 Citilink airline passengers as a sample from the population, employing a non-probability incidental sampling technique. The data obtained from the sample was analyzed using multiple linear regression through SPSS Version 25 software. The regression formulation in this study is asfollows:Y=-2.139 + 0,355X1 + 0,31X2 + 0,225X3 +0,285 + µ. From these equations, it can be seen that the most dominant variable affecting the Passenger's Decision is the Brand Image variable with a regression coefficient of 0.355. The R2 (R Square) test obtained results of 0.620 or 62.0% which means that Passenger Decisions are influenced by Brand Image, Passenger Decisions, Service Quality, and Perceived Price, which are 62.0% and other factors that influence Citilink passenger decisions at Jenderal International Airport Ahmad Yani Semarang by 38%.